Application of Boost Inverter For Grid Connected Fuel Cell Based Power Generation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The boost inverter architecture is used as a building block in this research to create a singlephase grid connected fuel cell (FC) system with low cost and compactness. In addition, tosupport the FC's sluggish dynamics, the proposed system includes battery-based energystorage and a dc-dc bidirectional converter. The voltage mode of the single phase boostconverter is maintained, but the low frequency current ripple is regulated by the currentmode. The battery provides the low frequency current ripple, which mitigates the impacts ofsuch ripple pulled straight from the FC. This technology, however, may work in either agrid-connected or independent mode. In grid linked mode, the boost inverter can regulate theactive (P) and reactive (Q) powers using a second order generalised integrator algorithm thatoffers rapid signal conditioning for single phase circuits. At the grid side, we may lower TotalHarmonic Distortion (THD). In addition, we have a backup storage device to accommodatethe sluggish dynamics of the FC sources that are all integrated into one system. To confirmthe performance of the proposed system, a design model and guidelines, simulation, andexperimental findings from a laboratory prototype are available